Fabrication and comparison of RO-like and NF-like forward osmosis membranes - Chen, Eugene Jian Hong. (2013)
Forward Osmosis (FO) technology is becoming popular due to its potential applications in many important fields and its numerous advantages. As such, there is a demand for high-performance FO membranes (i.e. high water permeability, A and low salt permeability, B). A few RO-like and NF-like membranes have been developed in literature and demonstrated good FO performance. Complicated influences of membrane properties on FO performance, depending on operational conditions were discussed in this study. To meet future FO applications, systematic comparison is necessary.